Contesting modernity in the German secularization debate Karl Löwith, Hans Blumenberg and Carl Schmitt in polemical contexts - Griffioen, Sjoerd 1987- (Brill's studies in intellectual history, 2022)
In 'Contesting Modernity in the German Secularization Debate', Sjoerd Griffioen investigates the polemics between Karl Loewith, Hans Blumenberg and Carl Schmitt on the role of religion in modernity. He analyzes their contribution to the development of the broader German secularization debate between the 1950's and 1980's. As this development is traced, special attention is paid to how after 1968 this debate increasingly centered on Schmitt's notion of political theology and its appropriation by the Left. This is evinced in the work of Jacob Taubes, who is opposed by Odo Marquard, assuming a Blumenbergian-secularist position in this new political landscape. Griffioen concludes with a methodological reflection on the value of 'Geistesgeschichte' and by identifying parallels with the contemporary discourse of postsecularism.